Stakeholders' Perceptions of a School-Based Eye Care Programme in Baltimore, MD. (4th May 2022) - Kretz, Alyssa M.; Vongsachang, Hursuong; Friedman, David S.; Callan, Jonathan; Wahl, Madison; Mukherjee, M. Rani; Neitzel, Amanda; Collins, Megan E.
ABSTRACT: Purpose: To explore stakeholders' perceptions of a school-based vision programme (SBVP). Methods: We conducted 20 focus groups with 105 parents and teachers at schools in Baltimore, MD, that participated in a SBVP. Facilitators used a semi-structured interview guide to discuss participants' perceptions of the SBVP. Focus groups were audio-recorded, transcribed, and coded using inductive thematic analysis. Results: Participant perceptions fell into three categories: benefits of school-based eye care, limitations of school-based eye care, and observation of impact. The majority of participants had positive comments about the programme; benefits included convenience (location, time, and cost), the comprehensive nature of the programme, the quality of the eyeglasses and ability to receive replacements, and a positive screening/exam experience. Limitations of programme impact were related to communication and organisation, the time to receive the glasses, missed instructional time, and uncertainty about screenings. Observations of impact included academic and classroom improvements, as well as visual and other health improvements. Conclusion: Parents and teachers reported mostly positive perceptions regarding the SBVP. Their appreciation for the convenience underscores that location, cost, time, and comprehensive services are crucial aspects for implementing a successful programme. To maximize impact, programs must also implement robust communication campaigns that integrate into the schools' workflow to help parents and teachers stay engaged in the process from start to finish.